Suppressing the Multiple Nucleation for the Uniform Growth of Perovskite Single‐Crystal Microplates Arrays toward High‐Performance Optoelectronic Devices. (21st October 2022) - Malo, Tehinke Achille; Lu, Zhengjun; Deng, Wei; Sun, Yuye; Wang, Chaoqiang; Pirzado, Azhar Ali Ayaz; Jie, Jiansheng; Zhang, Xiujuan; Zhang, Xiaohong
Abstract: The pursuit of high‐performance and integrated perovskite optoelectronic devices drives the development of efficient methods to pattern perovskite single crystals (PSCs). However, due to stochastic and multiple nucleation, PSCs obtained from traditional patterning methods still suffer from heterogeneous morphology and low crystallinity, resulting in unwanted large variation in the device performance. Herein, an effective and universal strategy is reported for the large‐scale patterned growth of high‐quality perovskite single‐crystal microplates with uniform size and thickness. By modulating the wettability of gold nanoparticles, nucleation energetic barriers are subtly regulated and thus intractably random and multiple nucleation are fundamentally suppressed, enabling the formation of homogeneous perovskite microplates with exceptional properties in terms of ultralow surface defect density (6.1 × 10 7  cm −2 ) and high carrier mobility (176 cm 2  V −1  s −1 ). In consequence, the photodetector array based on the patterned perovskite microplates exhibits a large photoresponsivity up to 615 A W −1, along with a low photocurrent variable coefficient <5.2%, which enables the realization of ultrasensitive and high‐contrast imaging functions. This patterning technique constitutes a major step toward the deployment of PSCs in integrated optoelectronic devices. Abstract : A universal strategy is developed to subtly regulate the nucleation energetic barriers for large‐scale patterning growth of high‐quality perovskite single‐crystal microplates with uniform morphology and exceptional electrical properties. Based on the perovskite single crystal arrays, high photoresponsivity and low device‐to‐device variation are achieved in the integrated photodetection circuits, enabling ultrasensitive, and high‐contrast imaging functions.